The Relationship between Cyberbullying Training Experience, Gender, and Depression among the Malaysian Adolescents during the COVID-19 Pandemic - Pang, Khong Yun *; Ku, Wen Li *; Teng, Jaclyn Hui Jie *; Lew, Ren Wen *; Ooi, Pei Boon * (MDPI, 2022)
The introduction of the online educational system during the COVID-19 pandemic has increased the vulnerability to cyberbullying incidents among adolescents. This study examined the relationship between cyberbullying training and depression among Malaysian adolescents during the COVID-19 pandemic. A total of 1356 Malaysian adolescents participated in the online survey. Results revealed that depression was significantly associated with cyberbullying training. This study concluded that cyberbullying training can protect individuals from depression caused by cyberbullying. Female adolescents were found more vulnerable to depression than males during the COVID-19 pandemic. Therefore, we advocate that cyberbullying training is essential to be enforced in the current Malaysian schools’ curriculum.